PrEP Awareness and Perceived Barriers Among Single Young Men who have Sex with Men - A. Bauermeister, Jose; Meanley, Steven; Pingel, Emily; H. Soler, Jorge; W. Harper, Gary (Current HIV Research, 2013)
Pre-exposure prophylaxis (PrEP) has the potential to help reduce new HIV infections among young men who have sex with men (YMSM). Using a cross-sectional survey of YMSM (N=1,507; ages 18-24), we gauged YMSM’s PrEP awareness and PrEP-related beliefs regarding side effects, accessibility, and affordability. Overall, 27% of the sample had heard about PrEP; 1% reported ever using PrEP prior to sex. In a multivariate logistic regression, we found that YMSM were more likely to have heard about PrEP if they were older, more educated, were residentially unstable in the prior 30 days, had insurance, or reported having at least one sexually transmitted infection in their lifetime. We found no differences by race/ethnicity, history of incarceration, or recent sexual risk behavior. In multivariate linear regression models, Black and Latino YMSM were more likely than Whites to state they would not use PrEP because of side effect concerns. YMSM were more likely to indicate that they would not be able to afford PrEP if they did not have insurance or if they had a prior sexually transmitted infection, PrEP rollout may be hindered due to lack of awareness, as well as perceived barriers regarding its use. We propose strategies to maximize equity in PrEP awareness and access if it is to be scaled up among YMSM.
Keywords: Access